2013
DOI: 10.1177/0954405413482304
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical modeling sensitivity analysis of electrically assisted forming

Abstract: Recent research by the authors has resulted in the conception of several methods of accounting for direct electrical effects during an electrically assisted manufacturing process, where electricity is applied to a conductive workpiece to enhance its formability characteristics. This modeling and analysis strategy accounts for both mechanical effects and heat transfer effects due to the applied electrical power. This study presents a sensitivity analysis and explanation of several key material and process input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…3) and conduction length. This has been also demonstrated in terms of the thermo-mechanical modeling sensitivity analysis of EA forming by Bunget et al [22]. Since a parabolic function can be used to simulate the Joule heating temperatures at points   0, y along specimen gauge length [13,14], it can be written as,…”
Section: Joule Heating Temperaturementioning
confidence: 87%
“…3) and conduction length. This has been also demonstrated in terms of the thermo-mechanical modeling sensitivity analysis of EA forming by Bunget et al [22]. Since a parabolic function can be used to simulate the Joule heating temperatures at points   0, y along specimen gauge length [13,14], it can be written as,…”
Section: Joule Heating Temperaturementioning
confidence: 87%
“…While the current is flowing, the yield and flow stresses are significantly reduced, and the deformation limits are raised. 12,18 EAF has been shown to improve the forming limits and reduce the process forces of tensile tests, 12 compression tests 11 and deep drawing. 19 As electrons pass through the material, it is theorized that they aid dislocation motion in three ways: 20 by locally heating the area around dislocations, by increasing the kinetic energy deposited on the dislocation creating an electron ''wind force'' and by increasing the number of electrons, allowing bonds to be broken and formed more easily.…”
Section: Eafmentioning
confidence: 99%
“…While the current is flowing, the yield and flow stresses are significantly reduced, and the deformation limits are raised. 12,18 EAF has been shown to improve the forming limits and reduce the process forces of tensile tests, 12 compression tests 11 and deep drawing. 19…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of predicted and measured temperature indicated that the EP effect coefficient is different at different process conditions. Later Bunget et al 24 performed further analysis of the study carried out by Salandro et al 23 and reported that temperature-dependent specific heat needs to be considered to accurately predict the measured temperature profile.…”
Section: Introductionmentioning
confidence: 99%